New Synthetic Thrombin Inhibitors: Molecular Design and Experimental Verification - Sinauridze, Elena I.; Romanov, Alexey N.; Gribkova, Irina V.; Kondakova, Olga A.; Surov, Stepan S.; Gorbatenko, Aleksander S.; Butylin, Andrey A.; Monakov, Mikhail Yu.; Bogolyubov, Alexey A.; Kuznetsov, Yuryi V.; Sulimov, Vladimir B.; Ataullakhanov, Fazoyl I. (PLOS ONE, 2011)
Background The development of new anticoagulants is an important goal for the improvement of thromboses treatments. Objectives The design, synthesis and experimental testing of new safe and effective small molecule direct thrombin inhibitors for intravenous administration. Methods Computer-aided molecular design of new thrombin inhibitors was performed using our original docking program SOL, which is based on the genetic algorithm of global energy minimization in the framework of a Merck Molecular Force Field. This program takes into account the effects of solvent. The designed molecules with the best scoring functions (calculated binding energies) were synthesized and their thrombin inhibitory activity evaluated experimentally in vitro using a chromogenic substrate in a buffer system and using a thrombin generation test in isolated plasma and in vivo using the newly developed model of hemodilution-induced hypercoagulation in rats. The acute toxicities of the most promising new thrombin inhibitors were evaluated in mice, and their stabilities in aqueous solutions were measured. Results New compounds that are both effective direct thrombin inhibitors (the best KI was <1 nM) and strong anticoagulants in plasma (an IC50 in the thrombin generation assay of approximately 100 nM) were discovered. These compounds contain one of the following new residues as the basic fragment: isothiuronium, 4-aminopyridinium, or 2-aminothiazolinium. LD50 values for the best new inhibitors ranged from 166.7 to >1111.1 mg/kg. A plasma-substituting solution supplemented with one of the new inhibitors prevented hypercoagulation in the rat model of hemodilution-induced hypercoagulation. Activities of the best new inhibitors in physiological saline (1 µM solutions) were stable after sterilization by autoclaving, and the inhibitors remained stable at long-term storage over more than 1.5 years at room temperature and at 4°C. Conclusions The high efficacy, stability and low acute toxicity reveal that the inhibitors that were developed may be promising for potential medical applications.